AN ANALYSIS OF CHARACTERISTICS AND DIFFERENCES: ISLAMIC EDUCATION MANAGEMENT AND CONVENTIONAL EDUCATION MANAGEMENT - M. Zen Ma'arif; Nur Efendi (International Journal of Multidisciplinary Reseach, 2026)
Global educational developments demand that educational institutions adapt their paradigms, methods, and governance to remain relevant and effective. In this context, significant differences emerge between Islamic Education Management (IEM) and Conventional Education Management (CEM), spanning philosophical foundations, goal orientations, and operational practices. This study is designed to identify the characteristics, compare both educational management models, and analyze the opportunities for integration between the two. The research problem covers questions regarding the characteristics of IEM and CEM, their primary differences, and the potential for integrating the modernization of IEM with CEM principles without losing its Islamic value identity. The study employs a qualitative approach with a library research method. Data were gathered from textbooks, accredited scientific journals, and related regulatory documents, then analyzed using content analysis and comparative analysis to highlight the similarities, differences, and relevance of integrating both systems. The results indicate that IEM emphasizes the integration of spiritual values, prophetic leadership, and the goal of shaping insan kamil (the holistic human being), whereas CEM is oriented toward efficiency, effectiveness, productivity, and graduates' readiness to face industrial demands. Comparative analysis reveals that integrating IEM and CEM through the adoption of technology and modern management principles can enhance the quality of Islamic education without sacrificing religious values. These findings offer a balanced managerial framework between moral-spiritual values and the organizational effectiveness of modern education.